2022
DOI: 10.3389/fonc.2022.848406
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA RP11-138J23.1 Contributes to Gastric Cancer Progression by Interacting With RNA-Binding Protein HuR

Abstract: In spite of improvements in diagnostics and treatment of gastric cancer (GC), it remains the most common malignancy of human digestive system. It is now widely appreciated that long noncoding RNAs (lncRNAs) exert extensive regulatory effects on a spectrum of fundamental biological processes through diverse mechanisms. In this study, we explored the expression level and functional role of lncRNA RP11-138J23.1 in GC. Through bioinformatics analyses and in situ hybridization (ISH), we identified that RP11-138J23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, lncRNA RP11-138J23.1 enhances the metastatic and proliferative abilities of gastric cancer cells by increasing VAV3 mRNA stability via interaction with HuR. 52 The lncRNA ADORA2A-AS1 displays antitumor effects in HCC by binding to HuR and inhibiting the FSCN1/AKT axis. 35 Through bioinformatic analysis in this study, nine RBPs were identified with a high probability of binding to MEG3.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA RP11-138J23.1 enhances the metastatic and proliferative abilities of gastric cancer cells by increasing VAV3 mRNA stability via interaction with HuR. 52 The lncRNA ADORA2A-AS1 displays antitumor effects in HCC by binding to HuR and inhibiting the FSCN1/AKT axis. 35 Through bioinformatic analysis in this study, nine RBPs were identified with a high probability of binding to MEG3.…”
Section: Discussionmentioning
confidence: 99%
“…These clone‐based identifiers used to be displayed on Ensembl gene reports for human genes that had no HGNC symbol, but have now been removed completely and are not searchable in the current version of the Ensembl website. We recently found the following examples in the literature: AF178030.2 47 which has the approved HGNC symbol TRPS1‐AS1 ; RP11‐138 J23.1, 48 which has the approved symbol NIHCOLE ; RP11‐276H19.1 49 has approved symbol GAS1RR ; and RP3‐326I13.1 50 which has the approved symbol PINCR . We urge researchers to check genenames.org ahead of publication to see if there is an approved symbol for an lncRNA gene.…”
Section: A Cautionary Note On the Importance Of Approved Gene Nomencl...mentioning
confidence: 99%
“…following examples in the literature: AF178030.247 which has the approved HGNC symbol TRPS1-AS1; RP11-138 J23.1,48 which has the approved symbol NIH-COLE; RP11-276H19.149 has approved symbol GAS1RR; and RP3-326I13.150 which has the approved symbol PINCR. We urge researchers to check genenames.org ahead of publication to see if there is an approved symbol for an lncRNA gene.…”
mentioning
confidence: 99%
“…Previous reports indicated that lncRNAs regulated the stability of target mRNA and participated in the process of multiple disease by interacting with RNA-binding proteins (RBPs) [ 14 , 15 ]. For instance, lncRNA RP11-138J23.1 was reported to participated in the progression of gastric cancer through enhancing the stability of VAV3 mRNA by targeting HuR protein [ 16 ]. K-homology splicing regulatory protein (KHSRP), as a RBP, was demonstrated to be vital in the process of mRNA metabolism.…”
Section: Introductionmentioning
confidence: 99%